2020
DOI: 10.1007/s00127-019-01820-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of a measure of stigma towards occupational stress for mental health professionals

Abstract: Purpose Stigma is a common barrier to mental health professionals (MHPs) seeking help for occupational stress and burnout, although there is a lack of psychometrically sound tools to measure this construct. The current study aimed to develop and validate a scale (the Mental Health Professional Stigma Scale; MHPSS) for this purpose. Methods The MHPSS and related measures were completed by 221 Australian MHPs via online survey, with a subsample completing the MHPSS again 2 weeks after initial completion. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…This study responds to the research appeals of previous scholars by changing the perspective on workers' consciousness. These findings are consistent with those of a previous study showing that occupational stigma consciousness negatively impacts work-related outcomes (Clough et al. , 2020).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This study responds to the research appeals of previous scholars by changing the perspective on workers' consciousness. These findings are consistent with those of a previous study showing that occupational stigma consciousness negatively impacts work-related outcomes (Clough et al. , 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Understanding how Platform riders' workplace deviant behavior occupational stigma affects the target group, and how to respond, can better solve workplace problems (Van Laar et al, 2019). The present study concluded that occupational stigma consciousness negatively impacts work-related outcomes, such as occupational stress and burnout (Clough et al, 2020). Previous literature suggests that occupational stigma has a negative impact on employees in terms of cognition and behavior (Mikolon et al, 2021;Shigihara, 2018).…”
Section: Occupational Stigma Consciousness and Workplace Deviant Beha...mentioning
confidence: 54%
See 3 more Smart Citations